THE USE OF STORYTELLING TECHNIQUE IN TEACHING VOCABULARY TO YOUNG LEARNERS: A case study in One of English for Young Learner Courses in Bandung - Maulidia, Humaira Restu (2015)
Teaching English vocabulary for young learners should be adjusted to young learners' characteristics. Hence, this paper is conducted to investigate the implementation of storytelling technique in teaching vocabulary to young learners and to find out the benefits and the challenges faced by the teachers during the teaching and learning process in English for young learner course in Bandung. In this research, case study design is employed to get in depth understanding on how the activities in the classrooms are carried out. The data were obtained from non-participant classroom observation, interview, and field notes. The data collected from classroom observation and interview were transcribed and then analyzed by using framework for planning story-based work (Brewester, Ellis and Girrad, 2002). In addition, the data also were analyzed using the framework of activities for storytelling (Wright, 2008). The findings revealed that the teachers applied the four steps of storytelling technique in teaching vocabulary to young learners. The first step was the teachers' preparation (designing lesson plan, selecting stories, and setting the seat position). The second step was the activities before storytelling (introducing new vocabularies). The next step was the activities during storytelling (telling stories), and the last step was the activities after storytelling (reviewing the vocabularies given) (Wright, 2008). Another result was the use of storytelling can help students' attention last longer because the method employs stories that children like. Referring to findings, it is suggested that the storytelling is used in teaching vocabulary to young learners, to provide enjoyable learning environment and to give chance to children to enhance their vocabulary mastery. Pengajaran kosa kata bahasa Inggris kepada anak-anak sebaiknya disesuaikan dengan karakteristik anak-anak. Oleh sebab itu, Penelitian ini bertujuan utuk menginvestigasi penggunaan teknik storytelling dalam pengajaran kosa kata pada anak-anak dan untuk mencari tahu kelebihan-kelebihan serta kesulitan-kesulitan yang dihadapi para guru dalam proses belajar-mengajar di salah satu tempat les di Bandung. Dalam penelitian ini, studi kasus dilakukan untuk mencari tahu lebih medalam bagaimana aktivitas tersebut dilakukan di kelas. Data tersebut diambil dari non-partisipan observasi kelas, wawancara, dan catatan peneliti di kelas. Data yang sudah didapatkan melalui observasi kelas dan wawancara kemudian ditranskrip dan dianalisis menggunakan teori story-based (Brewster, Ellis, Girrad, 2002). Selain itu, data juga dianalisis menggunakan teori aktivitas-aktivitas dalam storytelling (Wright, 2008). Hasil dari penelitian ini menyatakan bahwa guru-guru mengaplikasikan empat tahap dalam penggunaan teknik storytelling pada anak-anak. Tahap yang pertama yaitu persiapan guru-guru sebelum mengajar (membuat lesson plan, memilih cerita, dan mengatur posisi duduk di kelas). Tahap yang kedua adalah aktivitas-aktivitas yang dilakukan sebelum memberikan storytelling kepada siswa (memperkenalkan kosa kata baru kepada siswa). Langkah selanjutnya yaitu aktivitas-aktivitas ketika menggunakan storytelling (bercerita), dan langkah yang terakhir adalah aktivitas-aktivitas yang dilakukan setelah storytelling (proses evaluasi) (Wright, 2008). Hasil selanjutnya menyatakan bahwa penggunaan storytelling dapat membantu siswa untuk mempertahankan fokus perhatiannya lebih lama ketika belajar karena anak-anak pada umumnya menyukai cerita. Berdasarkan temuan tersebut, penggunaan storytelling dalam pengajaran kosa kata bahasa Inggris pada anak-anak disarankan untuk membuat sebuah pembelajaran yang menyenangkan dan kontekstual dan meningkatkan kemampuan kosa kata pada anak-anak.